Individuals who text crisis text line: Key characteristics and opportunities for suicide prevention. Issue 3 (26th May 2022) - Pisani, Anthony R.; Gould, Madelyn S.; Gallo, Carlos; Ertefaie, Ashkan; Kelberman, Caroline; Harrington, Donald; Weller, Daniel; Green, Shannon
Abstract: Objective: Text‐based crisis services are increasingly prominent, with inclusion in the national 988 crisis number launching in 2022. Yet little is known about who uses them. This study seeks to understand the population served by Crisis Text Line (CTL), the largest crisis text service in the United States. Methods: Secondary data analysis was conducted on de‐identified Crisis Counselor reports, texter post‐conversation survey responses, and anonymized text conversation data from 85, 877 texters who contacted CTL during a 12‐month period. We examined Crisis Counselor's ratings of suicide ideation severity, texters' reports of race, gender, sexual orientation, recent mental health symptoms, and additional sources of help, and logs of frequency of contact. Results: 76% of texters were under 25. 79% were female. 48% identified as other than heterosexual/straight. 64% had only one conversation. 79% were above the clinical cutoff for depression and 80% for anxiety, while 23% had thoughts of suicide. 23% received help from a doctor or therapist, and 28% received help only from CTL. Conclusions: CTL reaches a highly distressed, young, mostly female population, including typically underserved minorities and a substantial percentage of individuals who do not receive help elsewhere. These findings support the decision to include texting in the forthcoming national 988 implementation.